Heat stress promotes the accumulation of tomato yellow leaf curl virus in its insect vector by activating heat shock factor - Wang, Yu-Meng; Xie, Ting; He, Ya-Zhou; Cuellar, Wilmer Jose; Wang, Xiao-Wei (Springer, 2024)
High temperature tends to be a contributing factor to the spread of vector-borne viral diseases by enhancing vector competence. However, the underlying mechanisms of the increased virus transmission capacity of vectors under heat stress are still largely unknown. Tomato yellow leaf curl virus (TYLCV) is one of the most devastating plant DNA viruses worldwide and is transmitted exclusively by Bemisia tabaci. Here, we identified heat shock factor (HSF) as a key transcription factor that mediates TYLCV accumulation in whitefly vectors under heat stress. Quantitative analysis revealed that the amount of TYLCV DNA in whiteflies gradually increased with increasing temperature (above 38 °C). To determine the underlying mechanism, RNA-seq analysis was performed, which revealed that 1 h of heat stress caused a dramatic increase in heat shock protein (HSP) expression. Moreover, the whitefly HSP transcription factor HSF was shown to specifically interact with the intergenic region of TYLCV via yeast one-hybrid and dual-luciferase analyses. Additionally, the transcriptional activity of HSF gradually increased with increasing heat treatment tempera‑ ture, indicating a similar pattern of virus accumulation under heat stress. Knocking down HSF in whiteflies caused a significant decrease in TYLCV DNA and coat protein. Our results reveal the important role of HSF in mediating virus accumulation in insect vectors under high temperature and provide insights into how environmental factors affect plant virus‒vector interactions.